A Pragmatic Analysis of illocutionary Speech Acts in Standard Arabic with a Special Reference to Al-Ashter's "Epistle " - Jawad, Firas Abd Almunim (جامعة بابل, 2011)
Illocutionary speech acts in Standard Arabic makes the subject matter of the present study. It has some points of theoretical and cultural significance. Searle’s (1969) model to analyze the major speech acts of the discourse under study, namely, the ‘Epistle’ which is a letter from the Muslim Caliph Ali bin Abi-Talib fourteen centuries ago to one of his governors ,i.e., Malik Al-Ashter, the new ruler of Egypt then. That letter could be claimed to resemble the constitution. Most speech acts were ‘directives’ because of the instructive nature of the ‘Epistle’. Many other speech acts were miner rather than major. Van Dijk (1977b) model is adopted to analyze the miner speech acts. A further point of analysis is considered ,i.e,, (in)directness where the overwhelming majority of speech acts are used directly rather than indirectly under the influence of the instructive nature of the discourse under study
Keywords: اللغة العربية -- علي بن أبي طالب بن عبد المطلب ، ت 40 هـ -- الرسائل -- مالك بن الأشتر